Mitigasi Rantai Pasok Rumput Laut dengan Pendekatan House of Risk dan Fuzzy AHP di Kabupaten Maluku Tenggara - Wellem Anselmus Teniwut; Kamilius Deleles Betaubun; Marimin Marimin; Taufik Djatna (agriTECH, 2020)
Seaweed is among fishery commodities with great potential economy prospect. Southeast Maluku District is one of the main producers in Eastern region of Indonesia. Despite the high production since 2012, the number of farmers and the product has declined due to inadequate supply chain coordination and information dissemination among members. Therefore, this study aimed to mitigate the assymetric information in the region using the house of risk (HOR) to identify the risks to be addressed, and also provide response on the source of supply chain risk. Furthermore, Analytic hierarchy process (AHP) with fuzzy approach was used to determine the major factor, and then choose the best alternative to mitigate asymmetric information in the supply chain. Results showed there were five factors that contributed 70% risks. The results also indicated that dependence on local distributor was a factor that had to be prioritized and addressed. In addition, to mitigate the operational risks, findings showed it is necessary to establish seaweed farmers forum, which is the best approach based on the cost and effectiveness. This study also stated that local ,government of Southeast Maluku District was the main actor that helps to overcome the risks and asymmetric information problem. Therefore, the best alternative was to form an information center for seaweed cultivation, which will provide the knowledge of prices and potential buyer outside the region.